2015
DOI: 10.1017/s1368980015003572
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of micronutrient powder intake adherence in a pilot programme in Nepal

Abstract: Objective: Poor adherence to recommended intake protocols is common and a top challenge for micronutrient powder (MNP) programmes globally. Identifying modifiable predictors of intake adherence could inform the design and implementation of MNP projects. Design: We assessed high MNP intake adherence among children who had received MNP ≥2 months ago and consumed ≥1 sachet (n 771). High MNP intake adherence was defined as maternal report of child intake ≥45 sachets. We used logistic regression to assess demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 14 publications
8
52
0
2
Order By: Relevance
“…We found a smaller reduction in anemia, likely due to limited MNP coverage and adherence, which has been documented in other programmatic settings [12,13,14]. One major implementation barrier affecting Fortidom was a product quality problem that arose in the first few months of the program, which resulted in an unstable product that changed in consistency, color and taste.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…We found a smaller reduction in anemia, likely due to limited MNP coverage and adherence, which has been documented in other programmatic settings [12,13,14]. One major implementation barrier affecting Fortidom was a product quality problem that arose in the first few months of the program, which resulted in an unstable product that changed in consistency, color and taste.…”
Section: Discussionsupporting
confidence: 51%
“…Strengthening interventions to enhance consumption, particularly sustained consumption, has been identified as a key challenge facing MNP programs [34]; however, few studies have assessed which aspects of program implementation are associated with MNP coverage [12] and adherence [13]. We found that attending a CHW-IYCF talk and frequent exposure to IYCF-MNP radio messages were both associated with mothers’ initial use of MNP, but only CHW exposure was associated with continued MNP use.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The vast majority of published papers report on evaluations in the context of a pilot project (Creed‐Kanashiro, Bartolini, Abad, & Arevalo, 2015; Harris et al, 2012; Jefferds et al, 2015; Korenromp et al, 2015; Loechl et al, 2009; Mirkovic, Perrine, Subedi, Mebrahtu, Dahal, & Jefferds, 2016; Mirkovic, Perrine, Subedi, Mebrahtu, Dahal, Staatz, et al, 2015; Nguyen et al, 2016; Suchdev et al, 2010, 2013; Sun et al, 2011), with the exception of Bangladesh which reports on national programmes (Afsana, Haque, Sobhan, & Shahin, 2014; Angdembe, Choudhury, Haque, & Ahmed) and three large‐scale MNP distribution in refugee camps and in emergency contexts (de Pee et al, 2007; Kodish, Rah, Kraemer, de Pee, & Gittelsohn, 2011; Rah et al, 2012). …”
Section: Resultsmentioning
confidence: 99%